Faktor-faktor yang berhubungan dengan kurangnya keikutsertaan pasangan usia subur (pus) terhadap pemeriksaan test iva - Ramanda, Rafika; Imronah, Imronah; Putri, Ratna Dewi; Anggraini, Anggraini (JOURNAL OF Community Health Issues, 2023)
In Kupang City Health Center in Bandar Lampung the rate of early detection of cervical cancer IVA method in 2017 was 29.81% while in 2018 it increased by 31.91%, compared to the Sumur Batu Health Center coverage of cervical cancer early IVA method coverage in 2017 2017 amounted to 34.21% while in 2018 an increase of 36.13% (Profile of the Bandar Lampung City Health Office, 2018). The purpose of this study is to know the factors related to the lack of participation of fertile age couples on the Iva test for early detection of cervical cancer at the Blud Puskesmas Kupang Kupang Bandar Lampung in 2019. Type of Quantitative Research, with analytic survey research methods. The population in this study is a fertile human partner in the Community Health Center with a total of 2439 people. The samples in this study were 97 people. The sampling technique in this study used accidental sampling. Univariate data analysis, bivariate analysis using the chi-square test. The results of this study are known to the distribution of IVA behavior as many as 47 people (48.5%), low education as many as 62 people (65.9%), good knowledge by 49 people (50.5%), negative attitudes as many as 50 people (51 , 5%), known the relationship of Education of Fertile Age Couples (PUS) to the IVA Test P-value 0,000 <0.05 known to the relationship of knowledge of the Fertile Age Couple (PUS) to the IVA Test Examination to Detect Cervical Cancer Early in the Regional Public Health Service Board Kupang Kota Bandar Lampung in 2019P-value 0,000 <0.05. The relationship between the attitude of fertile age couples (PUS) to the examination of IVA test for early detection of cervical cancer in the Kupang District Public Health Service Office in Bandar Lampung in 2019P-value 0,000 <0.05. It is recommended for health workers to improve their knowledge, attitudes, education as a form of midwifery that can be done to improve the knowledge and attitude of mothers as an effort to prevent cervical cancer. Keywords: Knowledge, education, attitudes, IVA behavior Di Puskesmas Kupang Kota Bandar Lampung angka cakupan deteksi dini kanker serviks metode IVA pada tahun 2017 sebesar 29,81% sedangkan pada tahun 2018 mengalami peningkatan yaitu sebesar 31,91%, dibandingkan dengan Puskesmas Sumur Batu angka cakupan deteksi dini kanker serviks metode IVA pada tahun 2017 sebesar 34,21% sedangkan pada tahun 2018 mengalami peningkatan yaitu sebesar 36,13% (Profil Dinas Kesehatan Kota Bandar Lampung, 2018). Tujuan dari penelitian ini adalah diketahui Faktor-Faktor Yang Berhubungan Dengan Kurangnya Keikutsertaan Pasangan Usia Subur (Pus) Terhadap Pemeriksaan Test Iva di Blud Puskesmas Kupang Kota Bandar Lampung Tahun 2019. Jenis Penelitian Kuantitatif, dengan metode penelitian survey analitik. Populasi dalam penelitian ini adalah pasangan usia subur yang ada di Puskesmas yang berjumlah 2439orang. Sampeldalam penelitian ini adalah sebanyak 97 orangTeknik pengambilan sampel dalam penelitian ini menggunakanaccidental sampling. Analisa data univariat, analisa bivariat menggunakan uji chi-square. Hasil penelitian ini adalah diketahui distribusi perilaku IVA melakukan sebanyak 47 orang (48,5%), pendidikan rendah sebanyak 62 orang (65,9%), pengetahuan baik sebesar 49 orang (50,5%), sikap negatif sebanyak 50 orang (51,5%), diketahui hubungan Pendidikan Pasangan Usia Subur (PUS) terhadap Pemeriksaan Test IVA P-value 0,000< 0,05 diketahui hubungan pengetahuan Pasangan Usia Subur (PUS) terhadap Pemeriksaan Test IVA untuk Mendeteksi Dini Kanker Serviks di Badan Layanan Umum Daerah Puskesmas Kupang Kota Bandar Lampung Tahun 2019P-value 0,000< 0,05. Diketahui hubungan sikap Pasangan Usia Subur (PUS) terhadap Pemeriksaan Test IVA di BLUD Puskesmas Kupang Kota Bandar Lampung Tahun 2019P-value 0,000< 0,05. Disarankan bagi tenaga kesehatan agar meningkatkan pengetahuan, sikap, pendidikan sebagai salah satu bentuk tindakan kebidanan yang dapat dilakukan untuk meningkatkan pengetahuan dan sikap ibu sebagai salah satu upaya mencegah terjadinya kanker servisk. Kata Kunci : Pengetahuan, pendidikan, sikap, perilaku IVA